Assessment of Citrullinated Myelin by 1H-MR Spectroscopy in Early-Onset Multiple Sclerosis - Oguz, K.K.; Kurne, A.; Aksu, A.O.; Karabulut, E.; Serdaroglu, A.; Teber, S.; Haspolat, S.; Senbil, N.; Kurul, S.; Anlar, B. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Myelin instability and citrullinated myelin basic protein have been demonstrated in the brains of patients with chronic and fulminating forms of multiple sclerosis (MS). Our aim was to trace citrulline in the brains of patients with early-onset MS by using proton MR spectroscopy (1H-MR spectroscopy).MATERIALS AND METHODS: A short-echo single-voxel 1H-MR spectroscopy by using the point-resolved proton spectroscopy sequence was performed in 27 patients with MS and 23 healthy subjects. Voxels of interest were chronic demyelinating lesions (CDLs, n = 25) and normal-appearing white matter (NAWM, n = 25) on T2-weighted imaging, and when available in patients with MS, enhancing demyelinating lesions (EDLs, n = 8). Frontal white matter (WM) was studied in control subjects. N-acetylaspartate, choline, and myo-inositol (mIns)-creatine (Cr) ratios and the presence of a citrulline peak were noted.RESULTS: Citrulline peaks were more frequently observed in patients with MS than in control subjects (P = .035), located in the NAWM in 8/25 (32%), in CDLs in 7/25 (28%), and in EDLs of 1/8 (12.5%) patients with MS. The presence of citrulline and measured metabolite/Cr ratios was not related to age at imaging, age at disease onset, duration of disease, or number of relapses. There was no significant metabolic difference between the NAWM of patients with MS and the WM of the control subjects. mIns/Cr was significantly greater in CDLs compared with the NAWM of patients with MS and the WM of healthy subjects.CONCLUSIONS: Citrulline was more frequently identified in the brains of patients with early-onset MS than in healthy subjects by 1H-MR spectroscopy, suggesting an association of increased citrullination of myelin proteins with demyelinating diseases.